Differences between bipolar and unipolar depression on Rorschach testing - Kimura H (Dove Medical Press, 2013)
Hiromi Kimura, Akemi Osaki, Rui Kawashima, Takeshi Inoue, Shin Nakagawa, Katsuji Suzuki, Satoshi Asakura, Teruaki Tanaka, Yuji Kitaichi, Takuya Masui, Nobuki Kitagawa, Yuki Kako, Tomohiro Abekawa, Ichiro Kusumi, Hiroyoshi Yamanaka, Kenzo Denda, Tsukasa KoyamaDepartment of Psychiatry, Hokkaido University Graduate School of Medicine, Kita-ku, Sapporo, JapanBackground: The bipolar-unipolar distinction in patients with a major depressive episode is the most important issue related to the diagnosis and treatment of mood disorders, but remains unresolved. This study was undertaken to compare bipolar and unipolar depression on Rorschach testing using the Comprehensive System with reference to healthy Japanese controls.Methods: Patients with bipolar or unipolar depression who had undergone the Rorschach test for routine clinical purposes were followed up naturalistically for a long period. Based on diagnostic confirmation after long-term follow-up, scores on this test for patients with bipolar and unipolar depression were compared with those published elsewhere for healthy Japanese controls.Results: The bipolar depression group showed significantly higher scores or positive findings in five variables of the Rorschach test, ie, WSum6, DR2 > 0, (CF + C) > FC + 2, PureC > 1, and Populars > 7, as assessed using the Comprehensive System, than did the unipolar depression group and healthy controls. These scores did not differ between the unipolar depression and control groups.Conclusion: The results of this study show thought disorder or cognitive slippage and marked laxness in modulating emotion in bipolar depression, indicating the psychopathological characteristics of bipolar disorder.Keywords: bipolar depression, bipolar disorder, Rorschach test, thought disorder, unipolar depression